IlluminApp: Educational support tool for sustainable indoor illumination system reconversion for household applications (2019)
The illumination household represents an important percentage of electricity consumption in developing countries. The electricity consumption derived from residential illumination is strongly reduced by assuming cleaner and more efficient technologies. One of the Sustainable Development Goals (SDG) considers responsible consumption and production of goods and services, in which the authors have focused this study on lighting loads on households. For this matter, IlluminApp has been developed. It is an educational tool, which allows to identify the benefits of the illumination technology conversion to residential users, as well as, an estimation on energy savings and the retrofit cost reduction by using different light bulbs technologies. The application uses a simple cost and energetic model to estimate: payback time, CO2emissions reduction, money, and energetic savings. This software is available in English and Spanish. The objective of this paper is to discuss in detail the interfaces of this application and its main functionalities. © 2019 AISTI.